2015
DOI: 10.1002/pon.4008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term fear of recurrence in young breast cancer survivors and partners

Abstract: Background Fear of a breast cancer recurrence is the most prevalent and disruptive source of distress for long-term survivors and their partners. However, few studies have focused on predictors of fear of recurrence. The aim of this study is to test the efficacy of the Social Cognitive Processing Theory (SCPT) in predicting fear of recurrence in long-term breast cancer survivors diagnosed at age 45 or younger and their partners. Methods In a large cross-sectional study, breast cancer survivors (N=222) 3–8 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 35 publications
3
105
2
Order By: Relevance
“…This scale has previously been used as a marker for prolonged or incomplete cognitive processing (Cohee et al, 2015; Lepore, 2001; Mosher et al, 2012). The Cognitive Avoidance subscale consists of 7 questions with responses ranging from 0 (not at all) to 4 (extremely), with higher scores indicating more avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…This scale has previously been used as a marker for prolonged or incomplete cognitive processing (Cohee et al, 2015; Lepore, 2001; Mosher et al, 2012). The Cognitive Avoidance subscale consists of 7 questions with responses ranging from 0 (not at all) to 4 (extremely), with higher scores indicating more avoidance.…”
Section: Methodsmentioning
confidence: 99%
“…Just over half of young adult breast cancer survivors in one study reported moderate to high levels of FOR. 25 Another study comparing AYA survivors to controls found no differences in anxiety or depressive symptoms but the AYA survivors did report more PTSS. 26 Other cohorts of AYA’s that were much larger (between N=300 and N=6000) found that AYA’s reported more distress than controls.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 96%
“…31 FOR may be maintained in survivors if they are unable to talk about the cancer experience with their partners. 25 This highlights the importance both of opportunities to process the cancer experience and of tracking these symptoms at least annually in AYAs to identify those with a need for treatment before negative moods become chronic.…”
Section: Anxiety and Depression In Different Populations Of Survivorsmentioning
confidence: 99%
“…Fear, worry, or concern about this uncertainty, collectively called fear of cancer recurrence (FCR), has been associated with greater depression and poorer quality of life among cancer survivors . Studies also have reported that FCR among family caregivers sometimes is higher than that of their patients . Caregivers' FCR that their patient's cancer may return or progress has been associated with their own greater anxiety, depression, and loneliness, and a poorer quality of life as well …”
Section: Introductionmentioning
confidence: 99%